ANALISIS SEMIOTIKA PESAN POLITIK DALAM “IKLAN MARS PARTAI PERINDO” - Yulika Purwaningsih; Ucik Ana Fardila (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2018)
Media is often used for political tools. Media has an important role in the political process, the media can influence the number of elections that are extraordinary in terms of politics. Some people prefer a political actor who often appears on the media screen rather than being passive behind the media. Politics by using media is intended so that information in politics can spread widely. So this is often used by some political parties to campaign or market their parties. Politicians market their parties through advertisements. Political advertisements that are currently emerging, whether on television or other social media, are songs of identity or better known as mars from the Indonesian Unity Party (Perindo) which is headed by Hary Tanoesoedibjo who is also the owner of MNC Group. This ad is often aired on several television stations under the auspices of MNC Group, such as RCTI, MNCTV, GlobalTV (which has now changed to GTV). In this study, researchers used qualitative research using semiotic analysis methods. Semiotic analysis methods can be used to find out the purpose and purpose of advertising through symbols and signs that are often raised when the ad is displayed. The object of the research used was the advertisement of Mars of the Perindo Party, where data sources came from television shows and literature literature such as books, internet sites, and others related to the object of research. The results of this study are the effects of semiotic messages that are included in the Mars advertisements of Perindo Party so that they can generate confidence and sympathy and support from the people who see them, and this will end in vote support during elections.